PENGARUH METODE ROLE PLAYING TERHADAP PERKEMBANGAN EMOSI ANAK USIA 5-6 TAHUN DI TK GKPI TARUTUNG KOTA - Afri Anisa Panjaitan; Uranus Zamili; Adiani Hulu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The aim of this research is to determine the effect of the role playing method on the emotional development of children aged 5-6 years at the GKPI Tarutung City Kindergarten. The research hypothesis is: "The role playing method has a significant effect on the emotional development of children aged 5-6 years at the GKPI Tarut-ung City Kindergarten". The population is all 113 GKPI Tarutung City Kindergarten students. The research sample was determined using a purposive sampling technique, namely 28 class B2 students as the experimental class using the role playing method and 25 class B3 students as the control class using ordinary treatment (conventional class). This research method is a quantitative approach with an experimental method with a quasi-experimental research type with a nonequivalent control group design research design. The instrument used in this research was a 15 item questionnaire. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 0.7358 in the high category. And the average value for the control class is 0.4205, which is in the medium category. Then carrying out an independent test using the t test obtained a value of t = 5.828 > t table (α = 0.05; df = 42,767) = 2.021. Thus, it can be concluded that the research hypothesis is accepted, namely that the role playing method has a significant effect on the emotional development of children aged 5-6 years at the GKPI Tarutung City Kindergarten and H0 is rejected.